The Role of The Pentahelix Model in Enhancing Disaster Management Effectiveness and Post-Disaster Recovery in North Sumatra and Aceh (Inovasi, 2026)
This study aims to analyze the role of the Pentahelix model in enhancing disaster management effectiveness and post-disaster recovery in North Sumatra and Aceh. This research employs a mixed-methods approach that combines qualitative and quantitative methods. The qualitative approach was conducted through policy document analysis and literature review to examine the implementation of disaster governance at the regional level. Meanwhile, the quantitative approach applies Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze the relationships among the actors in the Pentahelix model and their influence on disaster management effectiveness and post-disaster recovery. The findings indicate that the involvement of Pentahelix actors—government, academia, business sector, community, and media—has a significant influence on disaster management effectiveness. Furthermore, disaster management effectiveness acts as a mediating variable that strengthens the relationship between multi-stakeholder collaboration and successful post-disaster recovery. The results highlight that strengthening collaboration among stakeholders through the Pentahelix model can enhance regional capacity to manage and recover from disaster impacts more effectively. Therefore, developing collaborative governance based on the Pentahelix model is an important strategy for strengthening disaster management systems at the regional level.